Development of microcrystalline cellulose based hydrogels for the in vitro delivery of Cephalexin. Issue 1 (January 2020) - Kundu, Debashis; Banerjee, Tamal
Abstract: Three hydrogels namely, microcrystalline cellulose (MCC), microcrystalline cellulose-carboxymethyl cellulose (MCC-CMC) and microcrystalline cellulose-xylan (MCC-xylan) are synthesized using ethylene glycol diglycidyl ether as crosslinker. For the chemical characterization, FT-IR spectroscopy is adopted, whereas gel fraction and swelling ratio are used for the physical characterization of the hydrogels. Coarse morphology of hydrogels is further visualized by microscopic observation. The rheological characterization proves that MCC-CMC gel withstands higher strain to resist permanent deformation than the other two gels. The hydrogels are used for the loading and in vitro release of Cephalexin. The in vitro delivery is carried out in various simulated body fluids such as phosphate buffer saline (PBS), artificial intestinal fluid (AIF) and artificial gastric fluid (AGF). MCC-CMC is observed to deliver Cephalexin individually 15% in AGF, 86% in AIF, 98% in PBS and 98% in consecutive buffers (AGF followed by AIF and PBS). Abstract : Chemical engineering; Biochemical Engineering; Chemical synthesis; Drug delivery; Rheology; Biomaterials; Hydrogel; Microcrystalline cellulose; Rheology; Cephalexin